Financial Management in Construction Industry - Kapasi, Anshul (2012)
Balfour Beatty PLC. is a UK based Public Limited Company (PLC), which has chosen us, a three member team of MBA students (class of 2011-2012) from the University of Nottingham, for a company based management project, wherein the team was assigned the mission to look at the market opportunities for the group's subsidiary, Balfour Beatty Rail in the GCC market. While the main project report presented by the team includes the analysis of the business environment, this individual report is directed to cover history and evolution of financial management , and assessment of risks associated with project management which could be useful for Balfour Beatty Rail and other firms alike.